Pengaruh Tata Letak dan Sirkulasi Ruang terhadap Keterlibatan Pengunjung: Studi Kasus Museum Fatahillah - Maya Yuhanda; Ghina Nurmalitasari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Museums are essential for preserving culture and history, especially in cities like Jakarta, which have a history that spans from prehistoric times to modern times. The Fatahillah Museum in Jakarta is the best place to learn history because it has a collection of artifacts, important documents, and thematic exhibitions. The museum is not only a center for education, but it also helps to promote local culture through various activities such as workshops and seminars. The main challenge to improving the visitor experience is poor layout and circulation of the space. The way visitors enjoy the collections on display in the museum is greatly influenced by the layout, including the way the space is arranged. The Fatahillah Museum uses a hub-and-spoke and linear layout to direct visitors in a systematic way. But there are some problems, such as limited space, unergonomic collections and a poor navigation system. The space is filled with unique but sometimes confusing vertical and horizontal circulation grooves due to the architectural style of colonial Dutch museums. Factors such as visibility, lighting, and ergonomics also play a role in improving visitor comfort. With over 615,000 visitors in 2023, this problem is becoming more apparent, especially during busy holidays. To address this, the layout must be optimized, modern navigation is used, and the design of the exhibition hall must be updated to become more interactive and help students learn. In addition, arranging the collection chronologically and thematically can help visitors understand the historical and cultural context of the museum's collections.